2022
DOI: 10.21203/rs.3.rs-1910265/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The spectrum of cardiovascular complications related to immune-checkpoint inhibitor treatment

Abstract: Background: The full range of cardiovascular complications related to the use of Immune checkpoint inhibitors (ICI) is not fully understood. We aim to describe the spectrum of cardiovascular adverse events (cvAEs) by presenting our real-world experience of the diagnosis and management of these complications. Methods: Two thousand six hundred and forty-seven (2647) patients were started on ICI treatment between 2014 and 2020. Data from 110 patients referred to the cardio-oncology service with a suspected cvAE w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The United States Food and Drug Administration has also approved several ICIs including tremelimumab, nivolumab, atezolizumab, avelumab, ipilimumab, pembrolizumab, and durvalumab [4]. While the benefits reaped with ICIs play a pivotal role in the treatment of lung cancer, recent studies have shown that ICIs may precipitate serious cardiotoxic events, such as myocarditis, pericarditis, arrhythmias, myocardial infarction (MI), and non-inflammatory left ventricular dysfunction [5][6][7][8][9][10]. Concern over poor cardiac outcomes is heightened by the extensive use of ICIs in lung cancer therapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…The United States Food and Drug Administration has also approved several ICIs including tremelimumab, nivolumab, atezolizumab, avelumab, ipilimumab, pembrolizumab, and durvalumab [4]. While the benefits reaped with ICIs play a pivotal role in the treatment of lung cancer, recent studies have shown that ICIs may precipitate serious cardiotoxic events, such as myocarditis, pericarditis, arrhythmias, myocardial infarction (MI), and non-inflammatory left ventricular dysfunction [5][6][7][8][9][10]. Concern over poor cardiac outcomes is heightened by the extensive use of ICIs in lung cancer therapy [5].…”
Section: Introductionmentioning
confidence: 99%